Perilaku Harga Daging Ayam Ras, Ayam Kampung, Ayam Petelur Dan Itik Di Pasar Atas Sarolangun Selama Periode Sebelum Dan Sesudah Tahun Baru 2023/2024 - M. Anggun Saputra; Afriani H; Indra Sulaksana (CV. SINAR HOWUHOWU, 2026)
This study aims to examine the price behavior of poultry meat at Pasar Atas in Sarolangun Regency during the periods leading up to and following the 2023–2024 New Year. A survey method was employed for this research. Primary data collected included trader characteristics and poultry meat price behavior before and after the New Year, while secondary data covered poultry meat production and consumption in Sarolangun Regency. The study focused on the prices of broiler chicken, free-range chicken, spent laying hen, and duck meat. Descriptive analysis was used to analyze the data. The results indicate price fluctuations across these poultry types during the pre- and post-New Year periods. Prices for broiler chicken, free-range chicken, spent laying hen, and duck meat tended to rise in the two weeks and one week prior to the New Year. Conversely, prices for these poultry types tended to decline in the two weeks and one week following the New Year. In conclusion, poultry meat prices exhibited an upward trend before the New Year and a downward trend after the New Year.